2012
DOI: 10.1007/s00216-012-5833-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of phosphatidylcholine hydroperoxides during copper oxidation of LDL and HDL by liquid chromatography/mass spectrometry

Abstract: 1-Palmitoyl-2-linoleoylphosphatidylcholine monohydroperoxide (PC 16:0/18:2-OOH) and 1-stearoyl-2-linoleoylphosphatidylcholine monohydroperoxide (PC 18:0/18:2-OOH) were measured by liquid chromatography/mass spectrometry (LC/MS) using nonendogenous 1-palmitoyl-2-heptadecenoylphosphatidylcholine monohydroperoxide as an internal standard. The calibration curves for synthetic PC 16:0/18:2-OOH and PC 18:0/18:2-OOH, which were obtained by direct injection of the internal standard into the LC/MS system, were linear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…choline, m/z 184 20,21 , but the MRM 790/184 could not distinguish the hydroperoxide positional isomers e.g. 1-palmitoyl-2-9-hydroperoxy-octadecadienoyl -sn-glycero-3-phosphocholine 16:0/9-HpODE PC and 1-palmitoyl-2-1 3 -h y d r o p e r o x y -o c t a d e c a d i e n o y l -s n -g l y c e r o -3-phosphocholine 16:0/13-HpODE PC .…”
Section: Ms/ms Analysis Of Standard Sq-ooh Isomers In the Absence Andmentioning
confidence: 99%
“…choline, m/z 184 20,21 , but the MRM 790/184 could not distinguish the hydroperoxide positional isomers e.g. 1-palmitoyl-2-9-hydroperoxy-octadecadienoyl -sn-glycero-3-phosphocholine 16:0/9-HpODE PC and 1-palmitoyl-2-1 3 -h y d r o p e r o x y -o c t a d e c a d i e n o y l -s n -g l y c e r o -3-phosphocholine 16:0/13-HpODE PC .…”
Section: Ms/ms Analysis Of Standard Sq-ooh Isomers In the Absence Andmentioning
confidence: 99%
“…Uchikata et al used this approach to measure oxidized PCs in liver from mice fed on a high-fat diet: As an example, the monoperoxide of SAPC was monitored by transitions from m/z 842.6 to 184.1, 808.4 (loss of H 2 O 2 ), and 824.4 (loss of H 2 O) (136). It is important to note that the loss of water is not a very specific transition, as it occurs for hydroxides and hydroperoxides, although it has been used in an SRM approach (50 -adducts, respectively (82,85), and an advantage is that two transitions of comparable intensity, one for each fatty acyl chain, should be detectable. The corresponding neutral loss of fatty acyl fragments is observed in the positive ion mode, and facilitates structural determination, though these signals are generally weak and very dependent on lipid structure.…”
Section: Application Of Targeted Ms Methods For Oxidized Phospholipidsmentioning
confidence: 99%
“…There are limited studies on direct analysis of ROOH in the literature. Using ESI-MS, Hui et al identified ROOH formed from the oxidation of cholesteryl ester, reporting ammonium and sodium adducts of the ROOH molecular ions under positive ion mode and acetate adducts of ROOH molecular ions under negative ion mode (Hui et al, 2012a;2012b). Reinnig et al (2009) identified ROOH using on-line ion trap mass spectrometry, proposing that neutral loss of 34 Da (loss of H 2 O 2 ) from the protonated 20 molecular ions is a characteristic fragmentation route for ROOH.…”
Section: Introductionmentioning
confidence: 99%